Hidrologia comparativa e perda de solo e água em bacias hidrográficas cultivadas com eucalipto e campo nativo com pastagem manejada - Lanza, Regis (2015)
The effect of forest plantations with eucalyptus on water resources in the Pampa biome it has been little studied, resulting in a lack of information related to these impacts especially on the watershed scale. The objective of this study was to evaluate the influence of land use on hydrological behavior of watersheds, quantifying the hydrological variables precipitation, plant interception, evapotranspiration, drainage, and flow into two paired watershed located in the Pampa biome, one of them with eucalyptus (BE) (75.8 ha) and one with grassland and livestock production (BC) (96.2 ha). The study was conducted between August 2012 and March 2015. In the watersheds, we installed rain gauges and equipment to monitor and quantify the hydrological variables and runoff plots to quantify the loss of water and soil. The meteorological data were obtained from a weather station installed in the area with eucalyptus. The flow in the watershed with eucalyptus was 60% lower compared to the grassland watersehd. Flow rates were higher in BC than in BE between 5 and 80% retention, indicating that the BC provides greater downstream volume of water 75% of the time. Watershed with grassland produced relative values of interception, evapotranspiration and deep drainage smaller by, respectively, 34.3, 23.4 and 15.3% compared to eucalyptus, which resulted in flow increase in this watershed. During the study period the partitioning of rain in eucalyptus stands provided interception, throughfall, streamflow, litter interception and effective precipitation of 19.8, 76.7, 5.1, 1.6 and 80.2% of the total precipitation, respectively. Water and soil losses in the plot scale were higher in watershed with grassland than in eucalyptus. These water and soil losses were related to rainfall and were higher in months of higher rainfall.